2021
DOI: 10.1021/acsestwater.1c00145
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing (Initial) Biotransformation Reactions as an Organizing Principle for Unraveling the Extent of Trace Organic Chemical Biotransformation in Biofiltration Systems

Abstract: Due to the low environmental concentrations and substance-specific behavior of trace organic chemicals (TOrCs), general mechanistic insights can hardly be gained from biotransformation studies with individual substances. In this study, we aimed to identify prevalent enzymatic reactions under different redox and substrate conditions in a well-defined laboratory-scale column system. Biotransformation of chemicals in the first column, which was characterized by a relatively high biomass and rapid depletion of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…We suspected that transformation of carbamazepine was sensitive to modifications at the 10−11 olefinic bond because it is the electron-rich site involved in abiotic and biotic reactions of carbamazepine, such as oxidation by ozone 37 and enzymatic metabolism in humans. 38 However, these results and those from other studies 8,36 suggested that predictions of metabolite fate based on parent compound behavior may be inaccurate and should be interpreted with caution. Analysis of porewater data collected after the treatment plant that supplied water to the wetland was upgraded suggested that nitrate-reducing conditions were not essential for trace organic contaminant removal in the horizontal levee.…”
Section: Environmentalmentioning
confidence: 78%
See 2 more Smart Citations
“…We suspected that transformation of carbamazepine was sensitive to modifications at the 10−11 olefinic bond because it is the electron-rich site involved in abiotic and biotic reactions of carbamazepine, such as oxidation by ozone 37 and enzymatic metabolism in humans. 38 However, these results and those from other studies 8,36 suggested that predictions of metabolite fate based on parent compound behavior may be inaccurate and should be interpreted with caution. Analysis of porewater data collected after the treatment plant that supplied water to the wetland was upgraded suggested that nitrate-reducing conditions were not essential for trace organic contaminant removal in the horizontal levee.…”
Section: Environmentalmentioning
confidence: 78%
“…We suspected that transformation of carbamazepine was sensitive to modifications at the 10–11 olefinic bond because it is the electron-rich site involved in abiotic and biotic reactions of carbamazepine, such as oxidation by ozone and enzymatic metabolism in humans . However, these results and those from other studies , suggested that predictions of metabolite fate based on parent compound behavior may be inaccurate and should be interpreted with caution.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on data from previous studies, we hypothesized that amide- and ester-containing MPs would be biotransformed rapidly and that amine- and ether-containing MPs would be biotransformed slowly. , To test this hypothesis, we selected a biotransformation rate constant of 0.5 d –1 as a threshold to define relatively fast and slow biotransformations. We found that, in aggregate and in agreement with our expectation, ester-containing MPs were biotransformed relatively fast and that ether-containing MPs were biotransformed relatively slowly.…”
Section: Resultsmentioning
confidence: 99%
“…Cytochrome CYP450 enzymes (CYP450) are a superfamily of monooxygenases responsible for most phase-I biotransformation reactions, which may produce even more toxic metabolites than parent compounds in living organisms; although in most cases, the metabolic system can transform the hazardous environmental chemicals into readily extractable metabolites . In order to provide full support for scientific assessment of environmental health risk of pollutants during the whole life cycle, the development of methods for analyzing and predicting pollutant biotransformation, especially by human CYP450, has become a thriving field in environmental science. Emerging pollutants are synthetic or naturally occurring chemicals that are not commonly monitored or regulated in the environment with potentially known or suspected adverse ecological and human health effects . The continuing onslaught of emerging pollutants has provided a tremendous source of new projects and also yielded needs for new mechanistic explanations of their biotransformation .…”
Section: Introductionmentioning
confidence: 99%